1992
DOI: 10.1017/s0022215100118535
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation with Ki-67: An application to salivary gland tumours

Abstract: Using Ki-67, a monoclonal antibody, the proliferating capacity of 15 salivary gland tumours, including nine pleomorphic adenomas, four adenoid cystic carcinomas, one mucoepidermoid carcinoma and one acinic cell carcinoma was determined immunohistochemically, using normal salivary gland tissue as a control. The frequency of Ki-67 positive cells was 4.7 per cent in the normal salivary gland and one per cent in pleomorphic adenomas, whereas the average frequency in malignant tumours was 18.3 per cent. Among adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 8 publications
3
21
2
Order By: Relevance
“…However, all these studies [14,16,19,22] like ours, demonstrate very consistently that solid adenoid cystic carcinoma has proliferation index values double those of more differentiated, cribriform and/or tubular forms.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, all these studies [14,16,19,22] like ours, demonstrate very consistently that solid adenoid cystic carcinoma has proliferation index values double those of more differentiated, cribriform and/or tubular forms.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies on salivary gland tumour proliferation have mostly been restricted to the group of adenoid cystic carcinomas and have used different methodologies, namely S-phase cytometric determination [16], Ki-67/MIB1 [14,19] and PCNA immunocytochemistry [22], which biases the comparison of the different results. However, all these studies [14,16,19,22] like ours, demonstrate very consistently that solid adenoid cystic carcinoma has proliferation index values double those of more differentiated, cribriform and/or tubular forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We tried to distinguish benign oncocytoma from malignant oncocytoma with Ki-67 immunostain, and there was a higher frequency of Ki-67-positive cells in malignant oncocytoma. Murakami et al [5] demonstrated that the frequency of Ki-67-positive cells was significantly higher in malignant salivary gland tumors (adenoid cystic carcinomas, mucoepidermoid carcinoma and acinic cell carcinoma) compared to that in benign tumors (pleomorphic adenomas) of the salivary gland. Skalova et al [6,7] reported that cell proliferation activity in acinic cell carcinomas and mucoepidermoid carcinomas in the salivary glands, assessed with Ki-67 staining, represented a significant prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 is a nuclear protein expressed in proliferating cells, except in those in the G0 period of the cell cycle [4]. The close correlation between the frequency of Ki-67-positive cells and the grade of malignancy has been well established in various subtypes of salivary gland tumors, with the exception of oncocytoma [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%